Integrating the continental Amazon : management report, November 2005 to October 2006 (ACTO BrasiliaBR, 2006)
Highlights the achievements of the Amazon Cooperation Treaty Organization in health, environment, science and technology, education, tourism, transport and communication and indigenous matters.
Keywords: REGIONAL ORGANIZATIONS